RETRACTED: Development of technology for producing functional fabric with variable structure - Khamraeva Sevarahon; Kadirova Dilfuza; Rakhimkhodzhaev Saidivoris (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001